Factors Associated with Family Retention or Involvement in Treatment of Persons with Severe Mental Illness: A Scoping Review - Tejas Vasava; Gobinda Majhi; D. Muralidhar; Devvarta Kumar (Indian Journal of Psychological Medicine, 2023)
Objective: A scoping review was conducted to detect the factors that affect family retention (FR) or involvement (FI) in the treatment of persons with severe mental illness (PwSMI) and to understand the gaps in this research area. Design: We included studies that described factors associated with FR/FI in the treatment of persons with PwSMI. English language articles available in full text, published until June 2022, were included. The literature search was carried out in four major electronic databases, such as PubMed, Scopus, ProQuest, and EBSCOhost, for 6 months from January 2022 to June 2022, which yielded 5442 articles, of which six (four primary studies and two secondary studies) were considered for the final scoping review as per the inclusion criteria. Results: Five major categories of factors were identified: (a) family level, (b) professional level, (c) mental health system level, (d) related to characteristics of the patient and illness, and (e) related to the external environment. Most studies described barriers to FI, while only a few elaborated on facilitators for FI/FR. Systemic and family-level factors were the major contributors to the barrier to FI and FR in the treatment of people with PwSMI. Conclusion: There is a dearth of literature in the field of FR/FI in the treatment of people with schizophrenia. More research is required so that holistic interventions can be designed and provided.